Information Technology Management of The World's Largest Firms in The Context of Digital Transformation: A Study of Automobile Corporation BYD - Lixin An; Tatiana Samuseva (Communications of International Proceedings, 2022)
Digitalization is changing the requirements for information technology. First, digitalization requires more and more sophisticated technologies. Second, the requirements for information technology are growing in all directions, and the main thing is cost reduction. The timing of entering the international innovation market has become critical for competing companies. Also, the role of security for companies is of paramount importance, since the more reliance on online, the more new vulnerabilities and potential losses. The digital transformation in the international arena has long brought about great changes. The development of information technology is rapidly developing and changing the entire structure of the world economy, markets for goods and services, labor, business processes of companies, as well as the functioning of financial markets. The novelty of the article lies in the analysis of the assessment of the impact of digitalization on the sustainable development of the company, which allows assess the degree of use of digitalization as a tool for achieving progress in the field of sustainable development at the level of an individual company and creates an information and analytical base for evaluating the effectiveness application of digital technologies by business and society as a whole. The purpose of the article is to improve the optimization of activities using digital technologies in the company.
Keywords: Information technology; business processes; digitalization; management; digital transformation; digital enterprise; digital platforms